Preparation of avian influenza H5N1 and Newcastle disease antigens for hemagglutination inhibition assay applications - Okti Nadia Poetri; Syaharani Salsabila; Nada Adinda Pebriana (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2026)
Background Avian influenza (AI) and Newcastle disease (ND) are major poultry diseases in Indonesia, where monitoring of vaccination efficacy commonly relies on the hemagglutination inhibition (HI) assay. The HI assay requires viral antigens, which are generally obtained commercially from PUSVETMA. However, independent antigen preparation would be beneficial for private laboratories. Objective This study aimed to prepare and validate in-house AI and ND antigens as HI assay reagents. Methods Viruses were propagated in embryonated chicken eggs (ECE), inactivated using buffered neutral formalin (BNF), precipitated with polyethylene glycol (PEG-6000), and preserved with glycerol. Validation was conducted by parallel HI testing of 24 chicken sera for AI and 22 chicken sera for ND using both in-house and PUSVETMA’s antigens. Antibody titers were analyzed using analysis of variance (ANOVA), with sensitivity (Se), specificity (Sp), and kappa (κ) tests performed for agreement. Results ANOVA revealed no significant differences in geometric mean titers between in-house and PUSVETMA’s antigens (P<0.05). Both the AI and ND in-house antigens demonstrated Se and Sp values of 100% and κ values of 1, indicating perfect agreement. Conclusion These findings confirm that in-house AI and ND antigens are comparable to their commercial counterparts and can serve as reliable and cost-effective reagents for HI testing in private laboratories.